Predictive validity of the Montreal Cognitive Assessment (MoCA) as a screening tool for on-road driving performance. (February 2015) - Kwok, Jade Chiu Wai; Gélinas, Isabelle; Benoit, Dana; Chilingaryan, Gevorg
Introduction: The objectives of this study are to determine (1) the ability of the Montreal Cognitive Assessment to predict on-road driving performance in drivers with a neurological condition and elderly drivers with suspected cognitive decline, and (2) the association between the performance on the Useful Field of View and the performance on the Montreal Cognitive Assessment. Method: This study used a retrospective design. Clients were included who had completed the Montreal Cognitive Assessment and the on-road driving evaluation from November 2006 to May 2009 ( n = 154) in a driving rehabilitation program in the Montreal Area. Total scores on the Montreal Cognitive Assessment, Useful Field of View risk categories, pass or fail outcomes from an on-road evaluation, as well as demographic and clinical characteristics were recorded from participants' medical charts. Results: The Montreal Cognitive Assessment was found to have a sensitivity of 84.5% and a specificity of 50% with a cut-off of ≤25. It was significantly associated with the Useful Field of View risk category. Conclusion: The Montreal Cognitive Assessment could be a valuable screening tool. However, its predictive validity is not strong enough to recommend its use as the sole instrument for identifying unfit drivers.